Adopsi Platform Digital pada UMKM Kuliner: Peran Persepsi Kemudahan, Kualitas Layanan Elektronik, dan Kepercayaan - Asrithoifah, Asrithoifah; Yusmedi Nurfaizal; Anisa Nur Andina (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
The rapid growth of internet usage in Indonesia has created significant opportunities for micro, small, and medium enterprises (MSMEs) to enhance business performance through online food delivery platforms. GoFood, a service integrated within the Gojek application, is currently one of the leading online food delivery providers in Indonesia. This study aims to examine the effects of perceived ease of use and e-service quality on usage decisions, with trust serving as a mediating variable, among culinary MSMEs in Purwokerto. A quantitative research design was employed using survey data analyzed with SPSS 27. Data analysis techniques included validity and reliability testing, classical assumption tests, multiple linear regression, t-tests, and coefficient of determination analysis. The findings reveal that perceived ease of use significantly influences usage decisions, while e-service quality does not have a direct effect. Trust significantly affects usage decisions and is positively influenced by both perceived ease of use and e-service quality. Furthermore, trust is found to mediate the relationship between perceived ease of use and usage decisions, as well as between e-service quality and usage decisions. These results highlight the pivotal role of trust in shaping MSMEs’ adoption decisions toward online food delivery services.